“He Beat Prisoners of War for the Slightest Violations ...”: Practice of Bringing Nazi Accomplices to Criminal Liability (Based on Archival Materials of the Federal Security Service of Russia in the Vologda Oblast) - ALEKSANDR L. KUZMINYKH (Пенитенциарная наука, 2023)
Introduction: the article examines the practice of bringing to criminal liability of accomplices of Nazi occupiers from among Soviet citizens after the end of the Great Patriotic War. Purpose: based on the analysis of the archival case to reveal the mechanism of criminal prosecution of collaborators. Methods: theoretical methods of formal and dialectical logic, empirical methods of description and interpretation, historical and biographical, textual and formal legal methods. Results: the study of archival materials demonstrates the tragedy of the fate of Soviet servicemen who were captured by the Germans during the Great Patriotic War. In relation to Soviet prisoners of war, the Nazis provided for a cruel regime that doomed them to gradual death from starvation and inhuman treatment. Persons who collaborated with the Nazis became accomplices of the criminal occupation policy. After the defeat of the German army and its surrender, most collaborators were sent to special (screening and filtration) camps of the NKVD (People’s Commissariat for Internal Affairs). The Smersh Counterintelligence Department carried out operational and investigative measures to establish and document the facts of treason to the Motherland and cooperation with the Nazi occupiers. Persons whose criminal activity could be confirmed by evidence were tried by a military tribunal on the basis of Article 58-1 “b” of the Criminal Code of the RSFSR and Article 2 of the Decree of the Presidium of the Supreme Soviet of the USSR “On penalties for Nazi villains guilty of murder and torture of Soviet civilians and captured Red Army soldiers, for spies, traitors to the Motherland from among Soviet citizens and for their accomplices” of April 19, 1943. As a rule, accomplices of Nazi crimes served their sentences in penal camps of the Gulag.